Emergence of novel nephropathogenic infectious bronchitis viruses currently circulating in Chinese chicken flocks. Issue 1 (2nd January 2016) - Xu, Qianqian; Han, Zongxi; Wang, Qiuling; Zhang, Tingting; Gao, Mengying; Zhao, Yan; Shao, Yuhao; Li, Huixin; Kong, Xiangang; Liu, Shengwang
ABSTRACT: The emergence of novel infectious bronchitis viruses (IBVs) has been reported worldwide. Between 2011 and 2014, eight IBV isolates were identified from disease outbreaks in northeast China. In the current study we analysed the S1 gene of these eight IBV isolates in addition to the complete genome of five of them. We confirmed that these isolates emerged through the recombination of LX4 and Taiwan group 1 (TW1) viruses at two switch sites, one was in the Nsp 16 region and the other in the spike protein gene. The S1 gene in these viruses exhibited high nucleotide similarity with TW1-like viruses; the TW1 genotype was found to be present in southern China from 2009. Pathogenicity experiments in chickens using three of the eight virus isolates revealed that they were nephropathogenic and had similar pathogenicity to the parental viruses. The results of our study demonstrate that recombination, coupled with mutations, is responsible for the emergence of novel IBVs.